Las universidades globales. ¿Sembrando las semillas del futuro o ancladas en el pasado?' - O´Hagan, Chris (Uni-pluriversidad, 2012)
Las universidades globales. ¿Sembrando las semillas del futuro o ancladas en el pasado?'